Letrozole or clomiphene citrate as first line for anovulatory infertility: a debate - George Korula; Kamath Mohan S (BMC, 2011)
Abstract Clomiphene citrate has been traditionally used as the drug of choice in treating women with anovulatory infertility. In the last decade letrozole, an aromatase inhibitor has emerged as alternative ovulation induction agent. Literature confirms that letrozole has a definitive role in anovulatory women who have not responded to the clomiphene therapy. However its role as an alternative to clomiphene as first line therapy continues to be debated. Although it is probable that the overall benefits of letrozole surpass clomiphene citrate, currently available data does not confirm this view. There is need for large well-designed trials.